Monitoring and predicting the influences of land use/land cover change on cropland characteristics and drought severity using remote sensing techniques - Zullyadini A. Rahaman (Tanjung Malim, 2023)
Monitoring and predicting the influences of land use/land cover change on cropland characteristics and drought severity using remote sensing techniques by Zullyadini A. Rahaman